2015
DOI: 10.1109/tcyb.2014.2381774
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Video Stitching Based on Fast Structure Deformation

Abstract: In computer vision, video stitching is a very challenging problem. In this paper, we proposed an efficient and effective wide-view video stitching method based on fast structure deformation that is capable of simultaneously achieving quality stitching and computational efficiency. For a group of synchronized frames, firstly, an effective double-seam selection scheme is designed to search two distinct but structurally corresponding seams in the two original images. The seam location of the previous frame is fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 62 publications
(128 reference statements)
0
9
0
Order By: Relevance
“…However, this assumption cannot guarantee the good alignment of the different fisheye videos after orthorectification, because there are always trees, vehicles, and other man-made objects on the ground, which will produce large object parallax and lead to obvious visual artefacts. On the other hand, as an elastic registration technology widely used in non-rigid medical image registration (Li et al, 2015), thin plate spline (TPS) can deal with the camera-model-independent spatial transformation of images by allowing local adaptation and constraint to certain continuity (Bookstein, 1989). To this end, this paper proposed an orthorectification constrained TPS technology to eliminate the serious distortion of fisheye videos and align them accurately, laying the foundation for seamless mosaic.…”
Section: Fisheye Video Correction Using Ortho Rec Tif Ica Tion Constr...mentioning
confidence: 99%
“…However, this assumption cannot guarantee the good alignment of the different fisheye videos after orthorectification, because there are always trees, vehicles, and other man-made objects on the ground, which will produce large object parallax and lead to obvious visual artefacts. On the other hand, as an elastic registration technology widely used in non-rigid medical image registration (Li et al, 2015), thin plate spline (TPS) can deal with the camera-model-independent spatial transformation of images by allowing local adaptation and constraint to certain continuity (Bookstein, 1989). To this end, this paper proposed an orthorectification constrained TPS technology to eliminate the serious distortion of fisheye videos and align them accurately, laying the foundation for seamless mosaic.…”
Section: Fisheye Video Correction Using Ortho Rec Tif Ica Tion Constr...mentioning
confidence: 99%
“…These softwares usually compute a 2D transformation relating two cameras, and then bring all pairs of video images into alignment for the post-production of stitched videos. To improve the quality of the stitched video, Li et al [31] found double-seam to eliminate intensity misalignment, and similar work has been presented for designing a content-aware adaptive blending [26]. Some works were presented to obtain better alignment results.…”
Section: Video Stitchingmentioning
confidence: 99%
“…When adding a temporal dimension camera stabilization, new challenges have to be considered in the performed interpolation. Efficiency [44], color correction [45], wider baselines [46], ghosting artifacts [47], video stabilization [48] among others. These have been the main focus points in recent research, with each different algorithm and proposed technique being more suited to different type of content.…”
Section: View Interpolationmentioning
confidence: 99%